GSDMD, an executor of pyroptosis, is involved in IL-1β secretion in Aspergillus fumigatus keratitis. (January 2021) - Zhao, Wenyi; Yang, Hua; Lyu, Leyu; Zhang, Jie; Xu, Qiang; Jiang, Nan; Liu, Guibo; Wang, Limei; Yan, Haijing; Che, Chengye
Abstract: The protein GSDMD is an important performer of pyroptosis and a universal substrate for the inflammatory caspase. However, the role and regulatory mechanism of GSDMD in Aspergillus fumigatus keratitis is remains unknown. Here we detected GSDMD protein in the cornea of normal and fungal-infected C57BL/6 mice. Human corneal epithelial cell (HCECs) were preincubated with a hydrochloride solution (IFNR inhibitor), ruxolitinib (JAK/STAT inhibitor), belnacasan (caspase-1 inhibitor) before infection with A. fumigatus conidia. Mice corneas were infected with Aspergillus fumigatus after pretreatment of GSDMD siRNA via subconjunctival injection. After, samples were harvested at specific time points and the expression of GSDMD and IL-1β was assessed by PCR, Western blot and immunofluorescence staining. Compared with the control group, we observed that the expression of GSDMD in fungal-infected mice cornea was significantly increased. After pretreatment with IFNR, JAK/STAT and caspase-1 inhibitors before fungal infection, the expression of GSDMD was significantly inhibited compared to the DMSO control in HCECs. Moreover, the GSDMD siRNA treatment have significantly weaken corneal inflammatory response, decreasing the proinflammatory factor IL-1β secretion and reducing neutrophils and macrophages recruitment in mice infected corneas. In summary, the data here provided evidences that GSDMD, an executor of pyroptosis, is involved in the early immune response of A. fumigatus keratitis. Additionally, the inhibition of GSDMD expression can affect the secretion of IL-1β and the recruitment of neutrophil and macrophages by blocking IFNR, JAK/STAT and caspase-1 signaling pathway. The protein GSDMD may emerge as a potential therapeutic target for A. fumigatus keratitis. Highlights: GSDMD, an executor of pyroptosis, is involved in A. fumigatus keratitis. GSDMD affects IL-1β secretion and neutrophil recruitment. The protein GSDMD may emerge as a potential therapeutic target for A. fumigatus keratitis.